Improving Indonesian Construction Consulting Services* - Tamin, Rizal Z.; Tamin, Puti Farida; Shahab, Faisol; Widiasanti, Irika; Oktavianus, Adrianto (ITB Journal Publisher, LPPM ITB, 2015)
Indonesian construction consulting services are facing a complex problem in fulfilling the nationâs expectations regarding high quality infrastructure development and the construction industryâs competitiveness. A study of this problem and a formulation of solutions to improve the situation are presented in this paper. A survey was carried out in Jakarta, West Java, East Java, and North Sumatra provinces to collect data related to this problem. A focus group discussion and a workshop with all stakeholders were conducted to formulate improvement actions that need to be taken. It was revealed that the problems faced include, among others, the limited number of professional engineers compared to the number of national consultancy companies, the uneven distribution of engineers in Indonesian regions, an imperfect procurement system, and low-quality work output in general. Recommended actions include improvement of the governmentâs role in consulting services nurturing and facilitation, development of partnerships, and amelioration of the professional engineer and consultant certification system.